Using sibling models to unpack the relationship between education and cognitive functioning in later life - Pamela Herd; Kamil Sicinski (Elsevier, 2022)
As the population ages and the prevalence of dementia increases, unpacking robust and persistent associations between educational attainment and later life cognitive functioning is increasingly important. We do know, from studies with robust causal designs, that policies that increase years of schooling improve later life cognitive functioning. Yet these studies don't illuminate why older adults with greater educational attainment have relatively preserved cognitive functioning. Studies focused on why, however, have been hampered by methodological limitations and inattention to some key explanations for this relationship. Consequently, we test explanations encompassing antecedent factors, specifically family environments, adolescent IQ, and genetic factors, as well as adult mediating mechanisms, specifically health behaviors and health. We employ the Wisconsin Longitudinal Study, which includes 80 years of prospectively collected data on a sample of 1 in every 3 high school graduates, and a selected sibling, from the class of 1957. Sibling models, and the inclusion of prospectively collected early and midlife covariates, allows us to address the explanatory and methodological limitations of the prior literature to better unpack the relationship between education and later life cognitive functioning. We find little evidence that early life genetic endowments and environments, or midlife health and health behaviors, explain the relationship. Adolescent cognition, however, does matter; higher educational attainment, linked to antecedent adolescent cognitive functioning, helps protect against lower levels of cognitive functioning in later life. Both adolescent cognition and education, however, independently associate with later life cognitive functioning at relatively similar magnitudes. Educational attainment's relationship to later life cognitive functioning is not simply a function of adolescent cognitive functioning.